Elaboración de un plan de negocios de una empresa dedicada a la producción de tratamientos para el control de pulgas a base de extractos naturales como Allium sativum, Chenopodium ambrosioides, Rosmarinus officinalis (2021)
This degree work makes a brief review of the problems that ectoparasites represent, which are part of the daily life of pets and therefore of their owner. Currently there are countless products on the market that ensure the elimination of these ectoparasites, however, they only treat a part of the flea cycle and their action is limited. In addition, pets such as dogs and cats may have adverse reactions to the active principles of these products such as: (symptoms of intoxication such as vomiting, diarrhea, neurological signs).